Laverty, Elisabeth 1. Interview about Anglican Cathedral of St. John the Baptist. - Barrett, Terra (2015)
Interview with Elisabeth Laverty, president of the Guild of St. Elizabeth. Laverty describes the background history of the Anglican Cathedral of St. John the Baptist and tells several stories relating to the cathedral